Severe acute respiratory syndrome coronavirus 2 detected in placentas of 2 coronavirus disease 2019-positive asymptomatic pregnant women-case reportAJOG MFM at a Glance - Jaime Sanchez, MD; Paulino Vigil-De Gracia, MD; Erika Guerrero, PhD; Melissa Gaitán, BSc; Cindy Fu, XX; María Chen-Germán, BSc; Rodrigo Villalobos, MD; Luis Coronado, MD; Alexander A. Martínez, PhD; Dimelza Araúz, BSc; Lisseth Saenz, MSc; Oris Chavarría, MSc; et al. (Elsevier, 2021)
There is limited evidence regarding severe acute respiratory syndrome coronavirus 2 infection in the placenta of pregnant women who tested positive, and if this could be a route for vertical transmission of the virus in utero. We present the cases of 2 pregnant women in their third trimester who were admitted for delivery by cesarean delivery and who, through universal screening, tested positive for coronavirus disease 2019. The maternal and fetal sides of the placenta were sectioned from both patients for viral analysis. Real-time polymerase chain reaction analysis of the placental-extracted RNA revealed a severe acute respiratory syndrome coronavirus 2 infection on the fetal side of the placenta in both patients. The virus was isolated from the patient with the lowest cycle threshold value on the fetal side of the placenta. Whole genome sequencing showed that the virus detected in this placenta was from the B1 lineage. Immunohistochemical analysis of the placental tissue detected severe acute respiratory syndrome coronavirus 2 in the endothelial cells of chorionic villi vessels proximal to both the maternal and fetal sides, with a granular cytoplasmic pattern and perinuclear reinforcement. Histologic examination of the placenta also detected a dense infiltrate of lymphoid cells around decidual vessels and endothelial cells with cytopathic changes, especially on the maternal side. Nasopharyngeal swabs from the infants that were subjected to reverse transcription quantitative polymerase chain reaction testing were negative for severe acute respiratory syndrome coronavirus 2 at 24 hours after birth. A follow-up analysis of the infants for immunoglobin G and immunoglobin M expression, clinical manifestations, and long-term developmental abnormalities is recommended.